PENGARUH KEPATUHAN IBU HAMIL TERHADAP KEBERHASILAN PENANGANAN PREEKLAMPSIA DI RUMAH SAKIT SANTA ELISABETH BATAM TAHUN 2014 - Liilis Sumardiani (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Darma Agung (LPPM_UDA), 2020)
Preeclampsia and eclampsia is a pregnancy complication caused directly by pregnancy itself. Successful handling of preeclampsia is determined by the compliance of pregnant women in antenatal care. Pregnant women who do not checkups cause no detection of high risk factors experienced during pregnancy. This is because women do not obey the doctor's orders to carry out checks ANC, diet and adequate rest.This study aims to identify and analyze the effect of maternal adherence (Antenatal Care, diet and rest) to the successful treatment of preeclampsia in Batam Elisabeth Hospital in 2014. The method used is explanatory survey with cross sectional design. The study population is the entire third trimester pregnant women. The research sample that is the entire third trimester pregnant women who checkups at Saint Elisabeth Hospital Batam as many as 47 people. Data were analyzed by multiple logistic regression.The results showed that there was influence compliance in the rest of the successful handling of preeclampsia (p = 0.002), whereas compliance in Antenatal care (p = 0.076) and compliance in the diet (p = 0.631) did not affect the success of treatment of preeclampsia.It is advisable for pregnant women to reduce the routine activities and undertake light activity in an effort to prevent preeclampsia, and it is expected that health professionals, in order to provide counseling for pregnant women who perform health checks, on the benefits of antenatal care, follow the diet and rest in improving maternal health during pregnancy.